2022
DOI: 10.1021/acsami.2c09937
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reduction Stabilizes the Single-Crystalline Ni-Rich Layered Cathode for Li-Ion Batteries

Abstract: The surface of the layered transition metal oxide cathode plays an important role in its function and degradation. Modification of the surface structure and chemistry is often necessary to overcome the debilitating effect of the native surface. Here, we employ a chemical reduction method using CaI2 to modify the native surface of single-crystalline layered transition metal oxide cathode particles. High-resolution transmission electron microscopy shows the 2 formation of a conformal cubic phase at the particle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…[ 55 ] Examination of XPS results from SIP‐NCM cathodes obtained from cycling at 4.4 V manifests that both characteristic peaks attributed to the adverse reactions are slightly elevated after 50 cycles (Figure S23, Supporting Information), probably catalyzed by high‐valence Ni. [ 56 ] The results show that both oxidative decomposition and Al corrosion reaction reinforce each other, leading to significant deterioration of interfacial compatibility in the TiP case. By contrast, the SIP‐derived coating confers to an inhibition of Al corrosion and EO oxidation simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 55 ] Examination of XPS results from SIP‐NCM cathodes obtained from cycling at 4.4 V manifests that both characteristic peaks attributed to the adverse reactions are slightly elevated after 50 cycles (Figure S23, Supporting Information), probably catalyzed by high‐valence Ni. [ 56 ] The results show that both oxidative decomposition and Al corrosion reaction reinforce each other, leading to significant deterioration of interfacial compatibility in the TiP case. By contrast, the SIP‐derived coating confers to an inhibition of Al corrosion and EO oxidation simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the unpolymerized monomers in the TiP case are susceptible to oxidative decomposition on the NCM cathode surface, which forms an inhomogeneous Li + barrier accompanied by LiTFSI decomposition and the generation of H + . [35,56] Furthermore, the decomposition reaction is aggravated by the presence of OH terminal groups in the TiP-derived SPE. [58] As a result, Al corrosion is induced by H + , which in turn causes the inferior interface to further accelerate the electrolyte decomposition.…”
Section: Sip Cyclic Voltammogram (Cv) Tests Of Al||li Electrochemical...mentioning
confidence: 99%
“…However, an in-depth investigation has demonstrated that electrode materials play a crucial role in the performance of lithium-based batteries. Finding appropriate electrode materials with high electronic conductivity, a large specific surface area, high efficiency, and great electrochemical performance is the major challenge toward developing efficient LIB storage systems. Currently, several materials have been investigated as LIB electrodes, including metal oxide, graphene, carbon nanotubes, , and so on. Due to their superior electrical conductivity and large pore volume, these materials are considered as good electrodes or support materials for lithium-based batteries.…”
Section: Introductionmentioning
confidence: 99%